Noise is a Loaded Gun of Violence: Thunder and Agression in Santo remedio of Rafael Courtoisie (Castilla. Estudios de Literatura, 2016)
This paper aims to study the implications which shows the phenomenon of noise connected to the violent act in the novel Santo remedio (2006) of Rafael Courtoisie. From a literary perspective, one comes to diverse disciplines as the sociology or the art in search of the links that connect noise and violence in the contemporary society, specially in the postmodernism. Likewise, theoretical as Julia Kristeva or Michel Foucault complete a theoric map that claims of explaining the micropolitics carried out by the protagonist of the work, who ends up by infecting of abject bodies his building. The hypothesis of the paper resides in connecting the violent acts done by Paul Green, protagonist of the novel, with the constant submission of his body and mind to the noise, from every aspect.